GENESIS OF SCIENTIFIC CONCEPTS OF INCLUSIVE ECONOMIC DEVELOPMENT - Zhukovska , Alina (Socio-economic relations in the digital society, 2025)
The article explores the genesis of scientific concepts of inclusive economic development. The topic's relevance is driven by the need to rethink traditional economic models in the context of modern global challenges, such as rising social inequality, environmental threats, digital transformation, demographic changes, and the consequences of pandemics and military conflicts. It is determined that inclusive development encompasses not only quantitative economic growth but also its qualitative characteristics, including social justice, economic mobility, environmental sustainability, and technological innovation. The research methodology is based on the systematic approach, historical-logical analysis, structural-functional analysis, comparative method, and classification-typological analysis. These methods made it possible to identify the patterns of the formation of inclusive development concepts, trace their evolution, and determine the interconnections between the key components of this approach.The study analyzes the main stages of the formation of economic development concepts, from theories of linear growth stages, structural transformations, and external dependence to modern approaches to sustainable development and the circular economy. Special attention is given to the concept of inclusive development, which is formed through the integration of social, economic, and environmental aspects. The key theoretical prerequisites, implementation mechanisms, and possible directions for the further transformation of the inclusive economic model are identified. The findings contribute to the expansion of the scientific discourse on the integration of various socio-economic groups into economic development processes and the formulation of effective strategies for inclusive growth at both national and international levels.
Keywords: economy; sustainable development; inclusive development; green economy; blue economy; silver economy; circular economy; sharing economy; digital economy